Construção e aplicação de índice de salubridade ambiental em aglomerados rurais - Braga, Débora de Lima (2021)
Environmental health is determined through the health status of a population, influenced by the socioeconomic and environmental conditions in which they live. One way to measure and analyze it is through the use of indexes and indicators. In this context, the Environmental Health Index emerged, which has been adapted to the particularities of the studied regions, losing one of the fundamentals of an index, comparability. In view of this scenario, the present study aims to propose a methodology for calculating the Environmental Health Index in rural agglomerates (ISARural) and apply it in rural communities in the state of Goiás. Based on the premise of the concept of environmental health, defined in this paper, and the specificities of rural areas. In order to achieve it, the methodology was carried out in four stages: bibliographic research to support the proposition of the concept and the elaboration of the forms used in this study; prior analysis for the proposition of an ISA Rural, with the participation of seven specialists; proposition of ISARural by the Delphi method, defined by the consensus of specialists in the previous step, starting with 168 specialists from the 27 Federative Units of Brazil; and the application in 43 rural communities (16 settlements, 21 quilombolas and 6 riverside) in the state of Goiás. ISARural was built in three stages: choosing and / or complementing the indicators suggested in the face-to-face discussion, weighting the indicators and selecting and weighting the sub-indicators. The specialists were divided by area of activity, which made it possible to select, adapt and / or create essential sub-indicators with specificity for each indicator. The proposed ISARural resulted in the composition of eight indicators, four related to basic sanitation, and the others, health, socioeconomic conditions, public services offered and housing conditions. The weight attributed to each indicator varied from 22.82%, for the water supply indicator, to 6.35% for the services indicator, and ISARural can be applied in its entirety or for the evaluation of each indicator individually. The application in rural and traditional communities in Goiás showed that 86.05% live in a situation of low health, highlighting the worst conditions for quilombola communities. In addition to identifying that the sewage component is the one that needs the most attention from the government. Finally, this study fulfilled the role of contributing to the proposition of an index in line with the concept of environmental health, which can be used within the scope of public policies as a condition for the application of priority resources, for planning and scenario general diagnosis of rural agglomerates.